2021
DOI: 10.1021/acsinfecdis.1c00345
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self-Adjuvanting, Cross-Protective, Stable Intranasal Recombinant Vaccine for Shigellosis

Abstract: With the acquirement of antibiotic resistance, Shigella has resulted in multiple epidemics of shigellosis, an infectious diarrheal disease, causing thousands of deaths per year. Unfortunately, there are no licensed vaccines, primarily due to low or serotype-specific immunogenicity. Thus, conserved subunit vaccines utilizing recombinant invasion plasmid antigens (Ipa) have been explored as cross-protective vaccine candidates. However, achieving cross-protection against Shigella dysenteriae 1, which caused multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…22,38−42 In a previous study, we demonstrated the self-adjuvanting protective efficacy of stabilized recombinant IpaC of Shigella dysenteriae 1 origin, which showed 100% survival against a high dose of heterologous Shigella flexneri 2a in BALB/c mice, in three intranasal doses. 43 In the current work, to further reduce the number of doses and increase patient compliance, the minimum protective dose of stabilized recombinant IpaC protein, determined in the earlier study, was encapsulated in biodegradable polymeric PLGA NPs, which was referred to as a single-dose nanovaccine. Because the gradual degradation of NPs is known to facilitate prolonged antigen presentation to immune cells, it is expected to raise a robust immune response.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…22,38−42 In a previous study, we demonstrated the self-adjuvanting protective efficacy of stabilized recombinant IpaC of Shigella dysenteriae 1 origin, which showed 100% survival against a high dose of heterologous Shigella flexneri 2a in BALB/c mice, in three intranasal doses. 43 In the current work, to further reduce the number of doses and increase patient compliance, the minimum protective dose of stabilized recombinant IpaC protein, determined in the earlier study, was encapsulated in biodegradable polymeric PLGA NPs, which was referred to as a single-dose nanovaccine. Because the gradual degradation of NPs is known to facilitate prolonged antigen presentation to immune cells, it is expected to raise a robust immune response.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17,47 ■ MATERIALS AND METHODS Bacterial Strains. As described in our previous report, 43 Escherichia coli DH5α and BL21 (DE3) Rosetta cells were procured from Microbial Type Culture Collection (MTCC), Chandigarh, India. Shigella strains, S. flexneri 2a (B294) (Sf2a) and S. dysenteriae serotype 1 (NT407) (Sd1), were obtained from the National Institute of Cholera and Enteric Diseases (NICED), Kolkata, India.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations